The role of self construal in perceptions of the severity of delinquent acts - S Rashidah Sulaiman (2010)
The present research investigates the role that self construal plays in perceptions of delinquent acts. In particular, this research is interested in whether the three levels of self construal proposed by Brewer and Gardner (1996) constitute three independent types of self construal, each with distinct outcomes. Two separate studies were conducted, one using an experimental paradigm to manipulate self construal, and the other measuring chronic self construal, both measuring perceptions of the severity of delinquent acts. Indeed in Study 1, collective self construal predicted the most variance in perceptions of severity over and above the effects of private and relational self-construal. In Study 2, participants in the collective self construal condition perceived delinquent acts as least severe, while participants with relational self-construa.l perceived delinquent acts as the most severe. These findings lend empirical support to the contention that the collective and relational self construals should be seen as separate components of self construal.